Sophie's masterpiece : a spider's tale - Spinelli, Eileen (Simon & Schuster Books for Young Readers, 2001)
Sophie the spider makes wondrous webs, but the residents of Beekman's Boarding House do not appreciate her until at last, old and tired, she weaves her final masterpiece.